Sengketa Pertambangan Terkait Divestasi Saham Antara Pemerintah Indonesia dengan PT. Newmont Nusa Tenggara - Risa Shoffia; J. Agung Indratmoko (Perspektif Administrasi Publik dan hukum, 2024)
Disputes in share divestment in Indonesia, such as the case between the Indonesian Government and PT. Newmont Nusa Tenggara, reflect the complexity of law and economy. This dispute was triggered by differences of opinion regarding the payment mechanism for shares sold by PT. Newmont Nusa Tenggara. The government rejects the payment scheme using funds from foreign capital owners such as PT. Bumi Resources Tbk, PT. Newmont Indonesia Limited, and Nusa Tenggara Mining Cooperation, because it is considered not in accordance with national interests. This study uses the Legal Research method with a normative juridical approach as explained by Prof. Peter Mahmud Marzuki. This conflict is caused by the weakness of the Work Contract, the unclear dispute resolution mechanism, and the lack of legal certainty regarding share divestment in Indonesia. The government and PT. Newmont Nusa Tenggara remain adamant with their respective schemes—the government wants national financial resources, while PT. Newmont offers foreign capital loans. This complicates communication and joint solutions. The main issues discussed are the legality of purchasing shares using foreign loans and the need for DPR approval in the divestment of shares in closed business sectors such as coal mining.